Therapeutic targeting of Krüppel-like factor 4 abrogates microglial activation - Kaushik, Deepak Kumar (BioMed Central, 2012)
BACKGROUND: Neuroinflammation occurs as a result of microglial activation in response to invading micro-organisms or other inflammatory stimuli within the central nervous system. According to our earlier findings, Krüppel-like factor 4 (Klf4), a zinc finger transcription factor, is involved in microglial activation and subsequent release of proinflammatory cytokines, tumor necrosis factor alpha, macrophage chemoattractant protein-1 and interleukin-6 as well as proinflammatory enzymes, inducible nitric oxide synthase and cyclooxygenase-2 in lipopolysaccharide-treated microglial cells. Our current study focuses on finding the molecular mechanism of the anti-inflammatory activities of honokiol in lipopolysaccharide-treated microglia with emphasis on the regulation of Klf4. METHODS: For in vitro studies, mouse microglial BV-2 cell lines as well as primary microglia were treated with 500 ng/mL lipopolysaccharide as well as 1 μM and 10 μM of honokiol. We cloned full-length Klf4 cDNA in pcDNA3.1 expression vector and transfected BV-2 cells with this construct using lipofectamine for overexpression studies. For in vivo studies, brain tissues were isolated from BALB/c mice treated with 5 mg/kg body weight of lipopolysaccharide either with or without 2.5 or 5 mg/kg body weight of honokiol. Expression of Klf4, cyclooxygenase-2, inducible nitric oxide synthase and phospho-nuclear factor-kappa B was measured using immunoblotting. We also measured the levels of cytokines, reactive oxygen species and nitric oxide in different conditions. RESULTS: Our findings suggest that honokiol can substantially downregulate the production of proinflammatory cytokines and inflammatory enzymes in lipopolysaccharide-stimulated microglia. In addition, honokiol downregulates lipopolysaccharide-induced upregulation of both Klf4 and phospho-nuclear factor-kappa B in these cells. We also found that overexpression of Klf4 in BV-2 cells suppresses the anti-inflammatory action of honokiol. CONCLUSIONS: Honokiol potentially reduces inflammation in activated microglia in a Klf4-dependent manner.